Decision Support System for Selecting the Best Santri Using the Simple Additive Weighting (SAW) Method - Fahlevi, Mohammad Reza; Kholil Rohman, Muhammad; Ali, Ircham; Muminin, Saeful (Fakultas Teknik Universitas Bhayangkara, 2026)
The evaluation of Santri in Islamic boarding schools plays an important role in measuring academic and non-academic achievements; however, the assessment process often lacks transparency and tends to be centralized, leading to subjective and inefficient decision making. This study proposes a Decision Support System (DSS) based on the Simple Additive Weighting (SAW) method to optimize the Santri evaluation process by considering 10 distinct academic and non-academic criteria in a systematic and objective manner. The research stages include requirement analysis, system design, implementation, and functional testing using the Black Box method to ensure reliable operation. The experimental results involving a dataset of 10 santri show that the proposed SAW-based approach is able to accurately automate the normalization and final score calculation processes. To validate the system's performance, the DSS-generated rankings were compared against the manual evaluation results from the boarding school administrators, achieving an accuracy rate of 80%. Furthermore, consistency testing demonstrated that the system maintains a stable and proportional ranking outcome when tested repeatedly. These findings confirm that the application of the SAW method significantly improves transparency, fairness, and efficiency in supporting decision making for Santri assessment.